Covalent Self‐Assembly and One‐Step Photocrosslinking of Tyrosine‐Rich Oligopeptides to Form Diverse Nanostructures. (8th April 2016) - Min, Kyoung‐Ik; Yun, Gyeongwon; Jang, Yoonjung; Kim, Kyung‐Rok; Ko, Young Ho; Jang, Hyung‐Seok; Lee, Yoon‐Sik; Kim, Kimoon; Kim, Dong‐Pyo
Abstract: We present covalently self‐assembled peptide hollow nanocapsule and peptide lamella. These biomimetic dityrosine peptide nanostructures are synthesized by one‐step photopolymerization of a tyrosine‐rich short peptide without the aid of a template. This simple approach offers direct synthesis of fluorescent peptide nanocages and free‐standing thin films. The simple crosslinked peptide lamella films provide robust mechanical properties with an elastic modulus of approximately 30 GPa and a hardness of 740 MPa. These nanostructures also allow for the design of peptidosomes. The approach taken here represents a rare example of covalent self‐assembly of short peptides into nano‐objects, which may be useful as microcompartments and separation membranes.